New Money in Rural Areas Land Investment in Europe and Its Place Impacts - Gallent, Nick; Hamiduddin, Iqbal; Juntti, Meri; Livingstone, Nicola; Stirling, Phoebe (Springer Nature Singapore : Imprint: Palgrave Pivot, 2019)
This book examines the flow of investment into rural land assets in Europe, particularly farmland, woodland and wineries, but extending also to leisure uses such as golf courses and theme parks. It explores the characteristics of investors in rural land and their motivations before undertaking an analysis of the place impacts of investment, viewing 'new money' as a potential development opportunity, delivering a variety of outcomes for local landscapes and communities. After providing introductory insights into rural land investment and the measurement of associated impacts, ten case studies - from different European locations - explore actual investment motives and local impacts. The book concludes with a synthesis of investment experiences and an assessment of the transformative changes brought to rural areas by the flow of new money.